The ACM/AIS IS2020 Competency Model for Undergraduate Programs in Information Systems - A Joint ACM/AIS Task Force Report - Leidig Paul; Salmela Hannu (The Association for Information Systems, 2022)
The Association of Computing Machinery (ACM) and the Association of Information Systems (AIS) along with the ISCAP EDSIG, recently released a joint taskforce report IS2020: A Competency Model for Undergraduate Programs in Information Systems. In this paper, the co-chairs of IS2020, the latest Information Systems curriculum guidelines, provide their insight on the problems presented with existing guidelines, illustrate the issue, and share their opinions that led to the release of these latest guidelines.